1989
DOI: 10.1002/1097-0142(19891115)64:10<2178::aid-cncr2820641033>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Adenocarcinoma of the small bowel in Lynch syndrome II

Abstract: Adenocarcinoma of the small bowel is rare and accounts for about 1% of all gastrointestinal tract cancer. This disorder has been identified in association with Crohn's disease, celiac disease, Peutz-Jegher's syndrome , and familial adenomatous polyposis. We report adenocarcinoma of the small bowel in nine patients from eight Lynch syndrome 11 extended pedigrees. Each affected patient was in the direct genetic lineage or manifested multiple primary cancers (stomach, colon, endometrium, and ovary) consonant with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

1990
1990
2010
2010

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(14 citation statements)
references
References 20 publications
0
13
0
1
Order By: Relevance
“…Consistent with colorectal cancer, 10% to 15% of cases of adenocarcinomas of the small intestine exhibit high microsatellite instability indicative of DNA mismatch repair dysfunction (42). Most germ line mutations reside at hMLH1 and hMSH2 loci (43). Individuals affected with hereditary nonpolyposis colorectal cancer are at increased risk of developing extra-colonic carcinomas in the small intestine, endometrium, pancreas, renal pelvis, stomach, liver and biliary tract, and ovary, and central nervous system gliomas.…”
Section: Morphology and Molecular Characteristics Of Enteric Neoplasmsmentioning
confidence: 99%
“…Consistent with colorectal cancer, 10% to 15% of cases of adenocarcinomas of the small intestine exhibit high microsatellite instability indicative of DNA mismatch repair dysfunction (42). Most germ line mutations reside at hMLH1 and hMSH2 loci (43). Individuals affected with hereditary nonpolyposis colorectal cancer are at increased risk of developing extra-colonic carcinomas in the small intestine, endometrium, pancreas, renal pelvis, stomach, liver and biliary tract, and ovary, and central nervous system gliomas.…”
Section: Morphology and Molecular Characteristics Of Enteric Neoplasmsmentioning
confidence: 99%
“…Lynch et al [6] identified nine individuals with small bowel adenocarcinoma from eight HNPCC extended pedigrees. In this series the average age at onset was 47 years, with lesions occurring in the jejunum (n = 6), ileum (n = 2), and duodenum (n = 1).…”
Section: Discussionmentioning
confidence: 99%
“…Aarnio et al [3], however, reviewed a larger cohort of 360 mutation carriers and found no cases of small bowel cancer. Cohort studies have reviewed the clinical pattern of small bowel cancers in HNPCC patients [4][5][6]. In addition to these larger series, many isolated case reports describe this association [7,8] Capsule endoscopy (CE) allows direct visualization of the entire small bowel with excellent safety and patient satisfaction [9].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the occurrence of a small bowel cancer in IV-11 and a ureteric cancer in IV 12, both very rare in the general population, are characteristic of the Lynch II phenotype. [22][23][24][25] The most peculiar feature of the Muir-Torre syndrome is the apparently indolent course of the cancers and the resulting relatively good prognosis. While no studies have directly addressed this phenomenon, a retrospective review of 120 persons showing the Muir-Torre phenotype estimated the median survival after first diagnosis of malignancy to be 12 years.…”
Section: Discussionmentioning
confidence: 99%